ANALISIS PENGARUH BUKTI FISIK, KEANDALAN, DAYA TANGGAP , JAMINAN DAN EMPATI TERHADAP KEPUASAN PASIEN YANG MELAKUKAN PEMERIKSAAN LABORATORIUM DI LABORATORIUM RSUD JARAGA SASAMEH BUNTOK - Ina Silvana; Hary Soegiri (JURNAL KINDAI, 2021)
Abstract: This study was carried out with the aim of knowing the effect of the quality of laboratory services on patient satisfaction in the laboratory of the JaragaSasamehBuntok Hospital. In this study, there were five independent variables, namely physical evidence, reliability, responsiveness, assurance and empathy and one dependent variable, namely laboratory patient satisfaction. The number of respondent in this study were 69 respondents, all of whom were outpatients and inpatients who underwent laboratory checks at the JaragaSasamehBuntok Hospital laboratory. The sampling method used is purposive sampling. The research data were then analyzed using multiple linear regression analysis techniques with the help of the SPSS 15.0 program. Based on the results in this study, the results of the analysis showed that simultaneously all independent variables (physical evidence, reliability, responsiveness, assurance and empathy) had a significant effect on laboratory patient satisfaction, and the partial analysis showed the results that physical evidence, reliability, responsiveness did not significant effect on laboratory patient satisfaction, while assurance and empathy significantly affect laboratory patient satisfaction. The most dominant variable affecting laboratory patient satisfaction is assurance. Keywords: Physical evidence, reliability, responsiveness, assurance, empathy, laboratory patient satisfaction.